Long non‐coding RNA reprogramming (lncRNA‐ROR) regulates cell apoptosis and autophagy in chondrocytes. Issue 10 (12th June 2018) - Yang, Zhongmeng; Tang, Yuxing; Lu, Huading; Shi, Bo; Ye, Yongheng; Xu, Guoyong; Zhao, Qing
Abstract: Long Non‐Coding RNA Reprogramming (lncRNA‐ROR) plays an important role in regulating various biologic processes, whereas the effect of lncRNA‐ROR in osteoarthritis (OA) is little studied. This study aimed to explore lncRNA‐ROR expression in articular cartilage and identify the functional mechanism of lncRNA‐ROR in OA. OA cartilage tissues were obtained from 15 OA patients, and 6 normal cartilage tissues were set as controls. Chondrocytes were isolated from the collected cartilage tissues. lncRNA‐ROR was knockdown in normal cells and overexpressed in OA cells. Cell viability was determined with Cell Counting Kit‐8 assay, and apoptosis was measured using flow cytometric analysis. Moreover, proteins and mRNAs involved in this study were also measured using Western blotting and quantitative real‐time PCR (qPCR). Level of lncRNA‐ROR was decreased in OA compared with normal chondrocytes, and overexpression of lncRNA‐ROR dramatically promoted cell viability of OA chondrocytes. In addition, knockdown lncRNA‐ROR inhibited apoptosis and promoted autophagy of normal chondrocytes. Moreover, lncRNA‐ROR inhibited the expression of p53 in both mRNA and protein levels. Furthermore, we revealed that lncRNA‐ROR regulated apoptosis and autophagy of chondrocytes via HIF1α and p53. The results indicated that lncRNA‐ROR played a critical role in the pathogenesis of OA, suggesting that lncRNA‐ROR could serve as a new potential therapeutic target for OA. Abstract : This study aimed to explore lncRNA‐ROR expression in articular cartilage and identify the functional mechanism of lncRNA‐ROR in OA. The results indicated that lncRNA‐ROR played a critical role in the pathogenesis of OA, suggesting that lncRNA‐ROR could serve as a new potential therapeutic target for OA.